Comparıson of I-Gel Laryngeal Mask and Endotracheal Tube Effects on Inflammatory Response in Hand Surgery - ArÄ±can, HÃ¼seyin; gan BakÄ±, Elif DoË˜; gra Koca, Halit BuË˜; Karasu, Necmettin; SÄ±vacÄ±, Remziye (Annals of Anesthesiology and Critical Care, 2019)
Background: Anesthesia and surgery together can cause endocrine and metabolic changes by creating a stress response. Objectives: This study aimed to compare the effects of two different applications of general anesthesia on the immune system by measuring serum cytokines in patients undergoing hand surgery. Methods: The study included 40 patients undergoing hand surgery with American Society of Anesthesiologists (ASA) physiological status I to III and ages between 18 and 65. The patients were randomly divided into two groups including I-gel LMA (group 1) and endotracheal tube (group 2). Blood samples were taken from all patients before anesthesia induction (T0), five minutes after the induction (T1), one hour postoperatively (T2), and 24 hours postoperatively (T3) for IL-1_, TNF-_, IL-6, and IL-8 analysis. The attempt numbers and the placement time of airway devices were noted in both groups.We also recorded patients’ perioperative OAB, pulse, saturation, SPI, and ETCO2. Results: There was no difference in TNF-_, IL-1_, IL-8, and IL-6 levels between the groups. When we compared trial periods, it was seen that I-gel LMA was statistically placed faster than laryngeal tube. Conclusions: One of the ways to reduce surgical stress is to minimize invasive procedures as much as possible. Although I-gel LMA did not reduce inflammation or stress response, placing it was faster than the endotracheal tube and this may give an advantage in favor of I-gel